Can short bouts of technique training improve sprint technique and performance in youth soccer players? - Sackey, S. A.; Navandar, A.; Kuitunen, S. (ISBS Proceedings Archive (Michigan), 2023)
This study aimed to investigate whether a technique-oriented intervention would result in improvements in sprint running technique and sprint performance in youth soccer players. Fourteen youth soccer players with pelvis and trunk control issues were divided into intervention and control groups. The intervention group did three weekly 15 minute running technique-oriented training sessions over seven weeks while their counterparts continued with their usual training programme. Sprint performance and technique were assessed before and after the intervention with a Laveg device and two video cameras, respectively, during a 40-m maximal sprint test. The players of the intervention group showed improved control of the trunk and pelvis (p=0.01) while no change was observed in the control group. Both groups showed a trend for improvement in sprint performance.